2004
DOI: 10.1002/ana.20287
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of multiple sclerosis with an anti–interleukin‐2 receptor monoclonal antibody

Abstract: We examined whether treatment with daclizumab, a humanized monoclonal antibody specific for the interleukin-2 receptor alpha chain, was safe and efficacious in relapsing-remitting and secondary progressive multiple sclerosis patients. Nineteen ambulatory patients with clinically active disease were treated for 5 to 25 months. Seventeen patients were not responding to other immunotherapies. Daclizumab was generally well tolerated. Sustained clinical improvement (10 patients) or stabilization (9 patients) was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
103
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(107 citation statements)
references
References 10 publications
4
103
0
Order By: Relevance
“…Multiple phase II studies of daclizumab in multiple sclerosis (MS) have reported significant efficacy in reducing contrast-enhancing lesions (CEL) and clinical disability. [1][2][3][4][5][6] Clinical efficacy of daclizumab treatment in MS has been linked to the expansion of CD56 bright NK cells, 3,6,7 which can regulate adaptive immunity by killing activated autologous T cells. 7 We describe a 42-year-old Caucasian woman (ZAP10) with a 5-year history of relapsing-remitting MS (RRMS) who completed a phase II clinical trial of daclizumab monotherapy in MS. 2 METHODS Magnetic resonance images were obtained at the height of the patient's symptoms using described methodology.…”
mentioning
confidence: 99%
“…Multiple phase II studies of daclizumab in multiple sclerosis (MS) have reported significant efficacy in reducing contrast-enhancing lesions (CEL) and clinical disability. [1][2][3][4][5][6] Clinical efficacy of daclizumab treatment in MS has been linked to the expansion of CD56 bright NK cells, 3,6,7 which can regulate adaptive immunity by killing activated autologous T cells. 7 We describe a 42-year-old Caucasian woman (ZAP10) with a 5-year history of relapsing-remitting MS (RRMS) who completed a phase II clinical trial of daclizumab monotherapy in MS. 2 METHODS Magnetic resonance images were obtained at the height of the patient's symptoms using described methodology.…”
mentioning
confidence: 99%
“…19 IL-2 is secreted by activated lymphocytes and stimulates production of other proinflammatory cytokines while it is also involved in lymphocytic proliferation. Daclizumab was initially approved for the prevention of renal allograft rejection as part of a combination regimen and evidence was progressively accumulated showing that this drug could also be effective in other diseases, such as non-infectious uveitis 30,31 and MS. [32][33][34][35][36][37][38] After demonstrating that the drug could be effective in animal models of the disease, 10 patients diagnosed with RRMS and secondary progressive MS (SPMS) were treated for six months with the combination of intravenous daclizumab (at 1 mg/kg/dose two weeks apart for the first two doses and once every four weeks thereafter for a total of seven infusions) and interferon beta after suboptimal response to the latter alone.…”
Section: Daclizumabmentioning
confidence: 99%
“…73,74 Two small, open-label (baseline versus treatment) phase II trials of daclizumab in MS have been published. 75,76 Both targeted RR MS patients with inadequate clinical and paraclinical response (i.e., MRI) to IFN-␤ preparations and used daclizumab as add-on therapy at the dose of 1 mg/kg of body weight administered as intravenous monthly infusions.…”
Section: Daclizumab (Zenapax; Anti-cd25 Ab)mentioning
confidence: 99%
“…75,76 Both the inhibition of brain inflammation by daclizumab and the reappearance of inflammation after cessation of the therapy developed gradually over a period of 2 to 3 months, suggesting that daclizumab induced gradual and prolonged immunomodulatory changes in vivo. A multicenter, randomized, doubleblinded phase II trial of daclizumab (2 mg/kg s.c. every 2 weeks) in 230 RR MS patients with incomplete therapeutic response to IFN-␤ (CHOICE trial) has been recently concluded.…”
Section: Daclizumab (Zenapax; Anti-cd25 Ab)mentioning
confidence: 99%